A contribution to the study of the concept of decoration in fine arts - rules and rightness - Žderić, Tamara D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
The ornament is part of every visual culture in the world. Its history goes back to early ages of human race. It is one of the most important fine art categories. The ornament was less important fine art category for a long time. The subject of this paper are varios types of ornament altogether with personal experience in creating ornament. The main aim was to reveal basis of ornament, its features and also to put in focus the importance of our attention in art process. Ornament has four categories determined by its appereance. Its complex forms, mathematical approach, and lots of details are features I found similar in my art practise (paintings or drawings with varios themes). The conclusions derived from this two varous types of ornament are contributions to examinations of its history through the eye of the artist.